A Robot, Meteorologist, and Amateur Forecaster Walk into A Bar: Examining Qualitative Responses to A Weather Forecast Delivered via Social Robot. Issue 6 (2nd November 2021) - Rainear, Adam M.; Jin, Xianlin; Edwards, Autumn; Edwards, Chad; Spence, Patric R.
ABSTRACT: The current study examines qualitative responses from participants about their opinions on a weather forecast delivered by a professional meteorologist, an amateur meteorologist, and a social robot standing in for a meteorologist. Through thematic analyses, this study identified that people evaluated each weather forecast agent's performance based on two major criteria: message factors and messenger factors. Two themes emerged from the category of message factors: an enjoyable/entertaining experience and commentary on the forecast content and information. Five themes were identified under the category of messenger factors: an expectancy violation or uncertainty which made participants uncomfortable, a distraction to the point it impeded focus on the forecast, vocalization concerns, unprofessional delivery, and commentary on the stimuli being "cute"/perceiving it as a joke. Findings further illustrate the expectancy violation people experienced while encountering a robot and/or amateur forecaster. Such knowledge will contribute to human-machine communication literature and offer pragmatic implications for technology development.